2022
DOI: 10.1007/s40789-022-00482-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical evaluation on debonding of fully grouted rockbolt under pull-out loading

Abstract: The axial loading in rockbolts changes due to stress redistribution and rheology in the country rock mass. Such a change may lead to debonding at rockbolt to grout interface or rupture of the rockbolt. In this study, based on laboratory experiments, ultrasonic guided wave propagation in fully grouted rockbolt under different pull-out loads was investigated in order to examine the resultant debonding of rockbolt. The signals obtained from the ultrasonic monitoring during the pull-out test were processed using w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The ultrasonic guided wave was excited at the A-end, and the wave was received at the F-end. The comparison between the numerical and experimental results is shown in Figure 4 [15]. The signal received at the other end was in good agreement with the experimental result, which indicated that the numerical model could simulate the guided wave propagation in grouted rockbolt systems.…”
Section: Experimental Verificationsupporting
confidence: 63%
See 3 more Smart Citations
“…The ultrasonic guided wave was excited at the A-end, and the wave was received at the F-end. The comparison between the numerical and experimental results is shown in Figure 4 [15]. The signal received at the other end was in good agreement with the experimental result, which indicated that the numerical model could simulate the guided wave propagation in grouted rockbolt systems.…”
Section: Experimental Verificationsupporting
confidence: 63%
“…Based on test results in the reference [15], the rockbolt experiences elastic ascent, yielding, hardening and complete slip without breaking. Therefore, the rockbolt is set as an elastoplastic material in ABAQUS.…”
Section: Modelling Of the Concrete Cement Mortar And Rockboltmentioning
confidence: 99%
See 2 more Smart Citations
“…To mitigate the influence of environmental and equipment noise on the detection results, several signal processing methods have been proposed for anchor rods NDT. These methods include Fourier transform (FFT) [3], wavelet filtering [4,5], variational mode decomposition-Hilbert Huang transform (VMD-HHT) [6], empirical mode decompositionspectral kurtosis denoising [7], HHT [8], AILPSA [9], grey cloud model [10], etc. Among them, FFT and wavelet filtering are earlier and widely applied signal processing methods.…”
Section: Introductionmentioning
confidence: 99%